Pengaruh Jam Tidur Terhadap Prestasi Belajar Mahasiswa - Riko Alamsyah; Izzatun Nisa Amalia; Eko Wahyu Utomo (CV. ITTC INDONESIA, 2023)
The phenomenon of sleeping hours on student learning achievement is a topic that needs to be discussed because sleeping hours alone will affect the achievements achieved by students. humans are required to have enough hours of sleep. because one aspect of student success in achieving learning achievement one of the basic needs is needed enough hours of sleep. Sleep is a basic need needed by everyone. Everyone needs enough sleep so that the body can function normally. In the sleeping state, the body performs a recovery process to restore the body's stamina to optimal conditions, so that it can carry out normal activities the next day. Students or students also need sufficient rest time to maintain the stability of their health, insufficient sleep hours will affect the learning process which of course will also affect their learning achievement as well. Learning achievement is the result of measuring and assessing students or students during the study period at an educational institution. In this study, the population that we used was students from the Faculty of Communication Sciences and Multimedia, Mercubuana University, Yogyakarta, class of 2021, while the sample was the Faculty of Communication Sciences students themselves. This type of research is quantitative research. The instrument used in this study was a questionnaire on the influence of hours of sleep and learning achievement. The data obtained was then analyzed using the SPSS software. The results showed that the value of Sig. the deviation from linearity is 0.711 which indicates that the variable X and Y have a linear relationship. The coefficient of R squared on the results of the linear regression test is 0.051, which means that 5.1% of learning achievement can be explained by students' sleeping habits. So from the data analysis that has been done, it can be concluded that student sleeping hours have an influence on FIKOMM student achievement at Mercu Buana University, Yogyakarta.